2021
DOI: 10.1007/s11325-021-02528-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of drug-induced sleep endoscopy in improving outcomes of barbed pharyngoplasty for obstructive sleep apnea surgery: a prospective randomized trial

Abstract: Purpose To observe the effectiveness of preoperative drug-induced sleep endoscopy in improving surgical results of patients undergoing single-level barbed pharyngoplasty surgery for OSA, using a prospective randomized model. Methods A single-center randomized controlled trial with two prospective arms was carried out to compare functional results in patients treated with barbed reposition pharyngoplasty (BRP) surgery without a preoperative drug-induced sleep endoscopy (DISE) evaluation vs patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 43 publications
(135 reference statements)
0
30
0
Order By: Relevance
“…Of the 482 remaining articles, 7 were included in the meta-analysis, including six observational studies 10,[17][18][19][20][21] and one randomised trial. 22 These seven articles represent 791 patients, 389 in the DISE group and 402 in the no DISE group. After reviewing the bibliography of the considered studies, no additional article was included.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 482 remaining articles, 7 were included in the meta-analysis, including six observational studies 10,[17][18][19][20][21] and one randomised trial. 22 These seven articles represent 791 patients, 389 in the DISE group and 402 in the no DISE group. After reviewing the bibliography of the considered studies, no additional article was included.…”
Section: Study Selectionmentioning
confidence: 99%
“…DISE was performed with propofol alone in four studies, 17,18,20,21 with various drugs in another (propofol alone, propofol + remifentanil or dexmetidine + remifentanil) 19 and one centre included in the multicentric study from Pang et al performed dexometidine-DISE. 10 The VOTE classification 23 was used in five studies, 10,17,19,20,22 a VOTE-adapted classification was used in one study, 21 and the classification system used was not described in the last study. 18 In all studies, surgery followed a previous treatment (PAP and/or mandibular advancement device) that failed or was not tolerated.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kezirian EJ applied DISE to observe the post-surgical UA collapse features in 33 individuals with uvulopalatopharyngoplasty(UPPP) failure and found that 45% of patients still had complete retropalatal collapse and 79% of patients had complete hypopharyngeal obstruction, confirming that residual palatal and glossal obstruction were important factors affecting the efficacy of UPPP [ 48 ]. Based on preoperative DISE assessment, surgeons could identify isolated velopharyngeal obstruction from combined velopharyngeal-hypopharyngeal obstruction, increasing the success rate of modified barbed pharyngoplasty from 60% to 83% [ 49 ]. In a study comparing two OSA cohorts with similar demographics and sleep test outcomes, compared with the group without pre-surgical DISE, preoperative DISE not only improved surgical success rate (86% vs 51%), but also decreased the proportion of multilevel surgeries (8% Vs 60%), that actually reduced unnecessary surgical damage and the risk of complications [ 50 ].…”
Section: Clinical Significances Of Disementioning
confidence: 99%
“…There are mainly three methods of endoscopy evaluation: awake electronic endoscopy, drug-induced sleep endoscopy (DISE), and natural sleep endoscopy. Drug-induced sleep laryngoscopy represents the gold standard for the diagnosis of obstructive site (9) and is often used for preoperative evaluation in ear, nose and throat (ENT) surgeries (10). However, it carries some risk due to the drugs, requires closer monitoring, and is more complex and expensive.…”
Section: Introductionmentioning
confidence: 99%